Esclerose tuberosa: a propósito de dois casos - CARVALHO, Juliana Maroja Seráfico de Assis (2023)
The tuberous sclerosis complex (TSC) is a genetic condition presented with the formation of hamartomas which may occur anywhere in the human organism, but especially in the central nervous system, kidneys, heart and skin and its early diagnosis is essential for patient’s follow-up and prevention and control of complications. During this research, clinical data have been obtained from two TSC patients, emphasizing the way the disease evolved and the control of its complications. In both cases, the clinical hallmarks were the epilepsy of moderate and hard control and the cognitive disability. Also, these features were joined by dermatological alterations, specifically the typical adenoma sebaceum. Both patients presented with renal manifestations, including systemic arterial hypertension and one case had severe renal insufficiency and evolved to death. The conclusion is that in both cases, the course of the disease was unfavorable, but with early diagnosis and adequate clinical and surgical management, the patient’s life quality can be improved while new promissing studies test more efficient therapeutic strategies to reduce the frequency and severity os seizures and other complications.